1992
DOI: 10.1677/joe.0.1340141
|View full text |Cite
|
Sign up to set email alerts
|

Long-term excess of endogenous calcitonin in patients with medullary thyroid carcinoma does not affect bone mineral density

Abstract: In a cross-sectional study of 39 patients with medullary thyroid carcinoma (MTC), we have investigated the effects of long-term calcitonin excess on bone mineral density. Bone mineral density was measured by dual X-ray absorptiometry at the lumbar spine between the second and fourth vertebra and by single photon absorptiometry at the distal forearm. The mean observation time of each patient between diagnosis of tumour and measurement of bone mineral density was 62.4 months (range 1-158 months). The mean calcit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…This is corroborated by fundamental observations during conditions of decreased or increased calcitonin levels, neither of which result in an appreciable phenotype in terms of calcium balance. For example, patients with medullary carcinomas of the thyroid (MTC), a tumor of the thyroid C-cells resulting in the hypersecretion of calcitonin, were shown to have normal bone mineral densities (1176). Animal studies further substantiate this conundrum.…”
Section: The Relevance Of Calcitonin For Calcium Homeostasismentioning
confidence: 99%
“…This is corroborated by fundamental observations during conditions of decreased or increased calcitonin levels, neither of which result in an appreciable phenotype in terms of calcium balance. For example, patients with medullary carcinomas of the thyroid (MTC), a tumor of the thyroid C-cells resulting in the hypersecretion of calcitonin, were shown to have normal bone mineral densities (1176). Animal studies further substantiate this conundrum.…”
Section: The Relevance Of Calcitonin For Calcium Homeostasismentioning
confidence: 99%
“…The hormone calcitonin is a known calcium-lowering factor, exerting its effect via the calcitonin receptor, and acting as an inhibitor of bone resorption [91]. However, in contradiction with the clearly defined pharmacologic mode of action, in patients with long-term excess of calcitonin due to medullary thyroid cancer bone mineral density is normal [92]. In line with physiological observations, the cell type-specific deletion of calcitonin receptor in mouse osteoclasts resulted in an increase in trabecular bone volume; furthermore, S1P release by osteoclasts was enhanced [89].…”
Section: Additional S1p-attributed Mechanisms Regulating the Bone Resmentioning
confidence: 99%
“…In most cross-sectional studies suppressive treatment had no effect on trabecular bone at central (Abugassa et al, 1993;De Rosa et al, 1995;Florkowski et al, 1993;Franklyn et al, 1992;Frusciante et al, 1998;Gam et al, 1991;Giannini et al, 1994;Görres et al, 1996;Hawkins et al, 1994;Langdahl et al, 1996;Lecomte et al, 1995;Lehmke et al, 1992;Marcocci et al, 1994;1997;Nuzzo et al, 1998;Schneider et al, 1995;Toivonen et al, 1998;Wüster et al, 1992) and peripheral sites (Radetti et al, 1993;Schneider et al, 1995;Wüster et al, 1992). The only study examining the calcaneus reported partial negative effects (Lehmke et al, 1992).…”
Section: Suppressive Treatmentmentioning
confidence: 99%
“…Results from cross-sectional studies on the effects of replacement therapy on trabecular bone were controversial, with no ef-fects at the lumbar spine (Franklyn et al, 1992;Gam et al, 1991;Hanna et al, 1998;Hawkins et al, 1994;Kung and Pun, 1991;Langdahl et al, 1996;Ribot et al, 1990;Schneider et al, 1995;Wüster et al, 1992) and ultradistal radius (Radetti et al, 1993;Schneider et al, 1995;Wüster et al, 1992), and reduced bone mineral density mainly in older and/or poor quality studies (Campos-Pastor et al, 1993; Demeester-Mirkine et al, 1990; Franklyn et al, 1994;Greenspan et al, 1991;Mirzaei et al, 1999;Schneider et al, 1994). The only study using QUS found lower ªbone mineral densityº at the calcaneus (Hadji et al, 2000).…”
Section: Replacement Treatmentmentioning
confidence: 99%
See 1 more Smart Citation